ABOUT STABLITY OF THE TRIVIAL SOLUTION OF A SYSTEM WITH IMPULSE ACTION - Гургула, Степан Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The question of stability of the trivial solution of a linear homogeneous system of the second order with constant coefficients which is center the impulse action on reaching a trajectory of a reaching a trajectory of a certain line passing through the origin is being studied.